Women's experiences of routine care during labour and childbirth and the influence of medicalisation: A qualitative study from Iran. (October 2017) - Pazandeh, Farzaneh; Potrata, Barbara; Huss, Reinhard; Hirst, Janet; House, Allan
Abstract: Objective: to understand women's experiences of routine care during labor and childbirth in a medicalised context. Design: twenty-six in-depth interviews were conducted during the late postpartum period and thematic analysis was applied. Setting: four public hospitals in Tehran with a high rate of births, providing services to low and middle income families. Participants: women who had a low risk pregnancies and gave a birth to a healthy infant by normal vaginal delivery. Findings: two main themes emerged: 'An ethos of medicalisation' which indicates that women's perception of childbirth was influenced by the medicalised context of childbirth. And 'The reality of fostered medicalisation' which illustrates the process by which interventions during labor affected women's pathway through childbirth, and how the medicalisation resulted in a birth experience which often included a preference for Caesarean Section rather than vaginal birth with multiple interventions. Implications for practice: contextual factors such as legal issues, state's regulations and the organisational framework of maternity services foster medicalised childbirth in Tehran public hospitals. These factors influence the quality of care and should be considered in any intervention for change. The aim should be a high quality birth experience with minimal interventions during normal vaginal delivery. A midwifery model of care combining scientific evidence with empathy may address this need for change. Highlights: The medicalised culture of childbirth made some women accept interventions during labour and childbirth as part of a 'normal' birth and Caesarean Section (CS) was a method of childbirth which women could select. Women's experiences of interventions during labour and childbirth promoted a pathway towards CS as a better option. Contextual factors such as legal issues, regulations and organisational frameworks of maternity services fostered medicalised childbirth.